KARAKTERISTIK HASIL TANAMAN KEDELAI AKIBAT VARIASI DOSIS HERBISIDA OXYFLUORFEN - Ramut, Anuar; Untari, Yulis; Sitinjak, Lentina; Sumoharjo, Deden; Nasrullah, Nasrullah (AGROSUSTAIN, 2023)
The right dose of herbicide is able to control weeds, further increasing soybeancrop yields. This study aims to obtain oxyfluorfen herbicide doses to control weeds insoybean plantations. The doses used are: 0; 0.4; 0.8; and 1.2 kg b.a ha-1. The designused was a non-factorial randomized block design with 3 replications. The variablesobserved were: number of plant pods1, number of plant seeds1, plant seed weight1, anddry seed yield. The results showed that a dose of 0.8 kg b.a ha-1 herbicide increasedseed weight1 and yield of dry soybean seeds.